Phosphoinositide 3‐kinase/protein kinase B inhibition restores regulatory T cell's function in pulmonary sarcoidosis. Issue 11 (3rd April 2019) - Zhang, Bin; Dai, Qianqian; Jin, Xuguang; Liang, Dongmei; Li, Xiaojie; Lu, Haiyan; Liu, Yu; Ding, Jingjing; Gao, Qian; Wen, Yanting
Abstract: Sarcoidosis is a systemic granulomatous disease associated with Th1/ regulatory T cells (Treg) paradigm. PI3K/Akt signaling, critical for maintaining Treg's homeostasis, is aberrantly activated in sarcoidosis patients. Here we tested the role of the PI3K inhibitors, LY294002 and BKM120, in immune modulation in experimental pulmonary sarcoidosis, concerning Th1/Th17/Treg immune profile detected by fluorescence‐activated cell sorting analysis or quantitative polymerase chain reaction, as well as the effect on Treg's suppressive functions. Our investigation showed abnormal activation of PI3K/Akt signaling both in lung and Treg in pulmonary sarcoidosis, along with decreased frequency and damaged function of Treg. Blockage of PI3K suppressed this signaling in Treg, rebalanced Th1/Treg, inhibited the production of inflammatory cytokines, and enhanced Treg's function. These results demonstrate the key role of the PI3K/Akt signaling in regulating Th1/Th2 rebalances and indicates that PI3K/Akt signaling is critical for the optimal Treg responses in pulmonary sarcoidosis. Thus, PI3K inhibitors have potential for therapeutic translation, and can be candidate for add‐on drugs to treat pulmonary sarcoidosis. Abstract : Blockage of PI3K suppressed this signaling in Treg, rebalanced Th1/Treg, inhibited the production of inflammatory cytokines, and enhanced Treg's function in sarcoidosis. PI3K/Akt signaling plays an important role in regulating Th1/Th2 rebalances and it is critical for the optimal Treg responses in pulmonary sarcoidosis.